Advantages of anchoring growth factors to materials for neural stem/progenitor cell proliferation. Issue 37 (7th September 2016) - Nakaji-Hirabayashi, T.; Fujimoto, K.; Kato, Y.; Kitano, H.; Inoue, Y.; Ishihara, K.
Abstract : We tried to clarify the mechanisms underlying immobilized-growth factor in NSPC regulation using approaches from materials science and cell biology. Abstract : Biomaterials modified with proteins such as growth and trophic factors are known to precisely regulate various cell and tissue functions. However, the mechanisms for regulation with proteins anchored to a substrate have not been extensively studied. Although we previously evaluated specific signal transduction from epidermal growth factor (EGF) anchored to a substrate to neural stem/progenitor cells (NSPCs), the internalization of immobilized-EGF and the continuity of signaling transduction were not discussed in detail. This information is important to determine the value of growth factor-anchored biomaterials in the regulation of cells. Here, we tried to clarify the mechanisms underlying immobilized-growth factor in NSPC regulation using approaches from materials science and cell biology. In this evaluation, we used EGF chimeric protein (EGF-His) and NSPCs, and found that EGF anchored to a substrate facilitated continuous signal transduction in NSPCs attached to the substrate. In addition, the anchored-EGFs were finally internalized into cells only when the proteins formed a complex with their receptors on cell membranes detached from the substrate. Finally, we concluded that continuous signal transduction by anchoring to the substrate and final internalization into cells with the detachment of anchored-proteins from a substrate are important events for efficient regulation of cell function.